Building capacity for sustainable research programmes for cancer in Africa - Adewole, Isaac (Nat Rev Clin Oncol, 2014)
Cancer research in Africa will have a pivotal role in cancer control planning in this continent. However, environments (such as those in academic or clinical settings) with limited research infrastructure (laboratories, biorespositories, databases) coupled with inadequate funding and other resources have hampered African scientists from carrying out rigorous research. In September 2012, over 100 scientists with expertise in cancer research in Africa met in London to discuss the challenges in performing high-quality research, and to formulate the next steps for building sustainable, comprehensive and multi-disciplinary programmes relevant to Africa. This was the first meeting among five major organizations: the African Organisation for Research and Training in Africa (AORTIC), the Africa Oxford Cancer Foundation (AfrOx), and the National Cancer Institutes (NCI) of Brazil, France and the USA. This article summarizes the discussions and recommendations of this meeting, including the next steps required to create sustainable and impactful research programmes that will enable evidenced-based cancer control approaches and planning at the local, regional and national levels.